2016
DOI: 10.1371/journal.pone.0154844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ocean Acidification and Temperature Increases on the Photosynthesis of Tropical Reef Calcified Macroalgae

Abstract: Climate change is a global phenomenon that is considered an important threat to marine ecosystems. Ocean acidification and increased seawater temperatures are among the consequences of this phenomenon. The comprehension of the effects of these alterations on marine organisms, in particular on calcified macroalgae, is still modest despite its great importance. There are evidences that macroalgae inhabiting highly variable environments are relatively resilient to such changes. Thus, the aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 36 publications
0
10
0
2
Order By: Relevance
“…The character * indicates the data that is closer to climate than weather goal, but still characterized as weather. areas (Ito et al, 2016;Orselli et al, 2018); studies of the impact of OA and other stressors in marine biota (Garrard et al, 2013;Rodríguez-Romero et al, 2014;Goulding et al 2017); and laboratory experiments (Orte et al, 2014;Scherner, et al, 2016;Schneider et al, 2018). Some examples of the BrOA studies done in the last five years associated with their classification based on the method precision are summarized in Table 2 and Figure 3.…”
Section: -mentioning
confidence: 99%
“…The character * indicates the data that is closer to climate than weather goal, but still characterized as weather. areas (Ito et al, 2016;Orselli et al, 2018); studies of the impact of OA and other stressors in marine biota (Garrard et al, 2013;Rodríguez-Romero et al, 2014;Goulding et al 2017); and laboratory experiments (Orte et al, 2014;Scherner, et al, 2016;Schneider et al, 2018). Some examples of the BrOA studies done in the last five years associated with their classification based on the method precision are summarized in Table 2 and Figure 3.…”
Section: -mentioning
confidence: 99%
“…Structurally complex, bioconstructions host macroinvertebrate communities characterized by remarkable abundance and species richness (Crowder and Cooper, 1982). In fact, they increase benthic diversity by providing hard substrates with a complex architecture for the species to settle on, hide and protect, thus the resulting assemblages are highly diverse and taxonomically complex (Jokiel et al, 2008). Previous studies showed that the physical characteristics of habitats affect community structure (MacArthur and MacArthur, 1961;Lawton, 1983;Ellner et al, 2001), with several studies demonstrating the linear relationship between increase in habitat complexity and increase in the diversity and abundance of its associated fauna (Kohn and Leviten, 1976;Heck and Wetstone, 1977;Downes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed the effect of pH and temperature on coralline algae, showing a stronger effect of temperature if compared with that of CO 2 concentration (Martin and Gattuso, 2009;Martin et al, 2013). Previous studies have shown a negative effect of global warming (GW) on recruitment (Kuffner et al, 2008), growth (Jokiel et al, 2008), and calcification (Gao et al, 1993;Semesi et al, 2009) of coralline algae leading to an increasing susceptibility to grazing by bioeroders (Steneck, 1986). Thus, GW and OA could have a dramatic consequence on species distributions (Harley et al, 2012;Bijma et al, 2013), possibly causing shifts in their abundance and geographical boundaries (Díez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of epiphytes only in February 2015 could indicate that higher temperature and lower wind speed, and thus, lower hydrodynamics, favoured fleshy algal growth, particularly Padina gymnospora . This species can grow in tropical temperatures similar to the ones that we recorded in the summer (Scherner et al ., 2016). Lower hydrodynamics have been associated with an increase in abundance and richness of biomass of maerl-associated algal species (Hily et al ., 1992; Hinojosa-Arango et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%